Symbols of Hopelessness in Joseph Conrad’s Heart of Darkness: A Study of Colonial Oppression - Kristine, Benensia Inka; Sriastuti, Anna (JELITA, 2025)
This research analyzes the symbols of hopelessness in Joseph Conrad's Heart of Darkness, focusing on the experiences of the Congolese under Belgian colonial rule. Using textual analysis grounded in Abram’s theory of symbols, the study examines how specific symbols—such as the iron collar, rifles, ivory, and the Congo River—embody the powerlessness, oppression, and suffering of the indigenous population. Thematic analysis reveals how these symbols represent the greed, destruction, and moral decay at the heart of colonialism. The iron collar symbolizes physical and psychological restraint, while the rifles signify the violence that enforces colonial dominance. Ivory represents the exploitation and greed driving colonialism, reducing both people and resources to commodities for profit. The Congo River functions as a path to both exploitation and despair for the Congolese, emphasizing the cyclical nature of their suffering. The findings highlight the stark contrast between the wealth of the colonizers and the degradation of the colonized, underscoring the pervasive hopelessness faced by the Congolese. This research contributes to postcolonial literary studies by offering a deeper understanding of the symbolic dimensions of Heart of Darkness and their broader implications for understanding colonial oppression, providing new insights into the moral and psychological impacts of imperialism.